Clinical Perspectives of Lithium’s Neuroprotective Effect - Rybakowski, Janusz K.; Suwalska, Aleksandra; Hajek, Tomas (Pharmacopsychiatry, 2018)
Evidence for a neuroprotective effect of lithium has accumulated over the last 2 decades, and this phenomenon has been regarded as an important mechanism of lithium action in mood disorders. It has been reflected by an increase in cerebral gray matter volume in lithium-treated subjects and by the favorable influence of lithium on cognitive functions. A neuroprotective effect of lithium also makes this ion a possible candidate for use as a therapeutic drug in neurology, especially in neurodegenerative disorders. In this paper, neurochemical mechanisms of neuroprotective action of lithium will be characterized. A possible association between the effect of lithium on brain structures reflected in neuroimaging studies, as well as on cognitive functions, and its neuroprotective action, will be considered. Data from experimental, epidemiological, and clinical studies have also pointed to an antidementia effect of lithium, bringing about some promise of using lithium in the treatment of mild cognitive impairment and Alzheimer’s disease. The results of attempts of employing lithium in other neurodegenerative disorders will also be discussed.
Keywords: lithium; neuroprotection; Alzheimer’s disease